Criminal Liability of Providers of Class I Non-Plant Narcotics Under Article 112 of Law Number 35 of 2009 on Narcotics (A Study of Decision Number 257/Pid.Sus/2025/PN.Mgl) - Jainah, Zainab Ompu; S, M. Zaqi Abiyaman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The illegal distribution of psychotropic substances in Indonesia, particularly in relation to the misapplication of Article 112 of Law Number 35 of 2009, constitutes a critical challenge to the effective implementation of essential regulations. A significant number of cases show that users or individuals who merely “possess” prohibited substances are sentenced to severe penalties without adequate consideration of their personal background, thereby necessitating a comprehensive understanding of criminological aspects and the burden of criminal liability. This study employs doctrinal legal research combined with empirical legal methods. Data were collected through observational research and literature review. The analysis was conducted using qualitative legal analysis through an explanatory approach. The findings reveal that the factors motivating selected offenders to act as providers include a combination of intrinsic and extrinsic motives, ranging from financial pressure to psychological deterioration caused by substance dependence. From a juridical perspective, the imposition of criminal liability in Decision Number 257/Pid.Sus/2025/PN.Mgl is consistent with the elements of intent (mens rea) and the defendant’s capacity to bear criminal responsibility. In sentencing, the judge emphasized substantive justice by imposing a prison sentence of three (3) years, taking into account that the narcotics were intended for personal use.